THE EFFECT OF HEALTH EDUCATION WITH THE LECTURE METHOD ON PREVENTION OF CKD (CHRONIC KIDNEY DISEASE) IN ADOLESCENTS - Ervina Rizki Wulan Suci; Ahmad Maftukhin; Evita Muslima Isnanda Putri; Siti Patonah (PT. Radja Intercontinental Publishing, 2026)
Chronic kidney disease (CKD) is a global health problem whose prevalence continues to increase and can cause long-term impacts starting from adolescence. Low knowledge and preventive behavior are among the factors contributing to the increased risk of CKD. This study aims to analyze the effect of health education using the lecture method on CKD prevention in adolescents. The study used a pre-experimental design with a one-group pretest-posttest approach. The study population was all 72 grade X students of SMAN 2 Bojonegoro, with a sample of 61 respondents selected using a purposive sampling technique. The research instrument was a questionnaire on CKD prevention knowledge and behavior. Data analysis was performed using the Wilcoxon Signed Rank Test with a significance level of 5%. The results showed that the proportion of respondents with good knowledge increased from 65.5% to 95.1%, while good preventive behavior increased from 45.9% to 59%. The median knowledge score increased from 6.00 to 10.00 and the median behavior increased from 50.00 to 55.00. The Wilcoxon test showed a p-value of 0.000 (p<0.05). In conclusion, health education using the lecture method significantly increased knowledge and behaviors related to CKD prevention in adolescents. Health education can be an effective promotive and preventive strategy for increasing awareness of kidney health from an early age